Measuring Cross-Sectorial Law Enforcement Capacity of Regulatory Agencies in Hungary - György GAJDUSCHEK (Transylvanian Review of Administrative Sciences, 2015)
The paper analyses the effectiveness of law enforcement by regulatory agencies in Hungary. Empirical data were collected from such diverse felds as consumer rights protection, construc-tion, road safety, labor regulation, etc. The data were analyzed using a simplifed rational choice model, looking for evidence of whether adminis-trative practices were effective in preventing ra-tional actors from breaking the law. The analysis robustly proves the ineffectiveness of regulatory activity, as the breaking of laws may yield, in a conservative estimate, 10 to 100,000 times more income than the expected monetary value of the fne. In brief, the government of Hungary is gen-erally unable to enforce its own laws. Though the paper makes use of data solely from Hungary, it aims to provide a methodology for measuring regulatory capacity more generally.